2008
DOI: 10.1038/onc.2008.331
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1, a SOX9 direct transcriptional target identified in the colon epithelium

Abstract: A deletion of the transcription factor SOX9 gene in the mice intestine affects the morphology of the colon epithelium and leads to hyperplasia. Nevertheless, direct transcriptional targets of SOX9 in this tissue are still unknown. A microarray analysis identified the tumor suppressor carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) as a possible SOX9 target gene and we demonstrate here that SOX9 upregulates CEA-CAM1 in human colonic cells. Moreover, CEACAM1 expression is reduced in colon of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
0
32
2
Order By: Relevance
“…As SOX9 deleted of its transactivation domain represses wild-type SOX9 activity in colon cancer cells (Blache et al, 2004;Bastide et al, 2007;Zalzali et al, 2008), we reasoned that such variants may well be expressed in colon cancer cells. We thus looked for a SOX9 splice variant resulting in a protein without the transactivation domain encoded by exon3.…”
Section: Sox9 Mrna Variants Are Expressed In Colon Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As SOX9 deleted of its transactivation domain represses wild-type SOX9 activity in colon cancer cells (Blache et al, 2004;Bastide et al, 2007;Zalzali et al, 2008), we reasoned that such variants may well be expressed in colon cancer cells. We thus looked for a SOX9 splice variant resulting in a protein without the transactivation domain encoded by exon3.…”
Section: Sox9 Mrna Variants Are Expressed In Colon Cancer Cellsmentioning
confidence: 99%
“…Moreover, SOX9 directly upregulates the tumor suppressor CEACAM1 (CarcinoEmbryonic Antigenrelated Cell Adhesion Molecule 1) in the intestine epithelium , while it downregulates the carcinoembryonic antigen (CEA or CEACAM5) in human colon carcinoma cells (Jay et al, 2005). SOX9 also increases apoptosis in colon tumor cells (Jay et al, 2005) and reduces cell proliferation rate, as illustrated by hyperplasia and dysplasia induced by Sox9 abrogation in the intestine epithelium (Bastide et al, 2007;Zalzali et al, 2008). The anti-proliferative activity of SOX9 was also evidenced in retinoid-treated breast cancer cell lines and melanomas (Afonja et al, 2002;Passeron et al, 2009;Muller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In intestinal epithelium, some reports have suggested an antioncogenic role for SOX9 (1,12,20,34), while others have demonstrated an oncogenic role (22,23). A recent genome-scale analysis of human colorectal cancer (CRC) identified SOX9 as one of the frequently mutated genes, and mutations in SOX9 were frame-shift or nonsense mutations (8).…”
mentioning
confidence: 99%
“…the binding of SOX9 to DNA (Bastide et al, 2007). This inhibition might result from an upregulation of groucho-related inhibitors of the β-catenin-Tcf complex (Bastide et al, 2007) and of CEACAM1, a direct SOX9 target (Jin et al, 2008;Leung et al, 2008;Zalzali et al, 2008). Indeed, the W143R SOX9 mutant, which is unable to bind DNA, is unable to inhibit the Wnt-APC pathway, although it is able to repress PKCα expression, as shown in the present study.…”
Section: Sox9-dependent Pkcα Repression Involves Sp1mentioning
confidence: 53%
“…However, the molecular mechanisms involved in these biological processes still remain to be elucidated. Up to now, CEACAM1 is the only SOX9 direct target identified in the intestinal epithelium whose gene expression is upregulated through the binding of the SOX9 HMG domain on a sequence similar to the in vitro characterized consensus sequence [A/T][A/T]CAA[A/T]G (Kamachi et al, 2000;Zalzali et al, 2008). The expression of genes encoding, for example, the CDX2 cell-differentiation marker, the carcinoembryonic antigen (CEA) or the tight-junction protein claudin 7 is inversely decreased in response to an overexpression of SOX9, but it was concluded that these repressions might be indirect, i.e.…”
Section: Introductionmentioning
confidence: 99%